Screening of Alpha-Thalassaemia 1 in Beta-Thalassaemia Carriers - Chong, Yi Min (2005)
Thalassaemia is an inherited blood disorder in which there is a reduction or absence in the synthesis of the globin chains of human Hb. Thalassaemia remains a public health problem in Malaysia, with many not knowing they carry the gene for thalassaemia. Individuals may be carriers of both a and Pthalassaemia. Concurrent a-thalassaemia 1 ( (~a / - -~~an*d) (3-thalassaemia (PA/POc) arriers are potential parents to offspring with Hb Bart's hydrops foetalis (--SEA/--SEaAn)d Fthalassaemia major (PO/PO)H. b Bart's hydrops foetalis results from homozygous state of a-thalassaemia 1 and Pthalassaemia major from homozygous Po. This study determines the frequency of concurrent carriers of alpha and betathalassaemia. The information gathered from this study will aid government agencies in policy-making, specifically on whether concurrent athalassaemia 1 identification needs to be done in any national screening programme for thalassaemia. Currently, most national screening programmes for thalassaemia including that in Malaysia concentrates on Pthalassaemia. Blood samples were analyzed using conventional haematological methods. These include full blood counts/red cell indices followed by Hb analysis to quantify Hb subtypes by high performance liquid chromatography (HPLC). A thalassaemia carrier is presumptively identified by a cut-off value of MCV40fL and MCHc27pg. On HPLC, those with HbA2>4.0% are identified as P-thalassaemia carriers. DNA was extracted from blood samples of the Pthalassaemia carriers and Gap-polymerase chain reaction (Gap-PCR) was done to identify the a-thalassaemia 1 molecular defect. The amplified product was run on 1.5% agarose gel by electrophoresis. The separated PCR product was then viewed under UV transillumination to identify the characteristic 570bp band for the a-thalassaemia 1 determinant. A total of 231 P-thalassaemia samples were studied. Eight were found to have concurrently inherited the a-thalassaemia 1 (-SEA) deletion, representing a carrier rate of 3.5%. The high carrier rate for a-thalassaemia 1 indicates the need for the implementation of DNA analysis to complement thalassaemia diagnosis in a population screening programme. The relative risk of Chinese Malaysian to a non-Chinese being a concurrent carrier of a-thalassaemia 1 (--SEA) and P-thalassaemia is 2.8 fold.